Effect of processing conditions on wood and glass fiber length attrition during twin screw composite compounding. Issue 15 (4th October 2019) - Dickson, Alan; Teuber, Laura; Gaugler, Marc; Sandquist, David
ABSTRACT: In this study, we compare the effect of twin‐screw extrusion processing on the attrition of wood fibers (WFs) with glass fiber. The effects of process variables and screw design on fiber length were investigated by performing a range of dead‐stop experiments where the extruder was stopped, opened‐up, and compound removed from the screw elements. Fibers, chemically extracted from the polypropylene matrix, were analyzed for length and width using a commercial fiber analyzer. It was found that WF length attrition and composite properties were less affected by screw design and twin‐screw processing conditions (feed rate and screw speed) than glass fiber. Length weighted fiber length and X50 length (a measure used in particle size analysis) were equally correlated with process conditions and composite performance for both fiber types. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48551. Abstract : Fiber length attrition along the extruder.